Failures in communication and information transfer across the surgical care pathway: interview study. Issue 10 (7th July 2012) - Nagpal, Kamal; Arora, Sonal; Vats, Amit; Wong, Helen W; Sevdalis, Nick; Vincent, Charles; Moorthy, Krishna
Abstract : Background and Objectives: Effective communication is imperative to safe surgical practice. Previous studies have typically focused upon the operating theatre. This study aimed to explore the communication and information transfer failures across the entire surgical care pathway. Methods: Using a qualitative approach, semi-structured interviews were conducted with 18 members of the multidisciplinary team (seven surgeons, five anaesthetists and six nurses) in an acute National Health Service trust. Participants' views regarding information transfer and communication failures at each phase of care, their causes, effects and potential interventions were explored. Interviews were recorded, transcribed verbatim, and submitted to emergent theme analysis. Sampling ceased when categorical and theoretical saturation was achieved. Results: Preoperatively, lack of communication between anaesthetists and surgeons was the most common problem (13/18 participants). Incomplete handover from the ward to theatre (12/18) and theatre to recovery (15/18) were other key problems. Work environment, lack of protocols and primitive forms of information transfer were reported as the most common cause of failures. Participants reported that these failures led to increased morbidity and mortality. Healthcare staff were strongly supportive of the view that standardisation and systematisation of communication processes was essential to improve patient safety. Conclusions: This study suggests communication failures occur across the entire continuum of care and the participants opined that it could have a potentially serious impact on patient safety. This data can be used to plan interventions targeted at the entire surgical pathway so as to improve the quality of care at all stages of the patient's journey.